(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Nurse-technician collaboration is integral to driving excellence in healthcare, profoundly impacting clinical practice and patient outcomes. This paper explores the multifaceted impacts of nurse-technician collaboration, focusing on improved patient care, enhanced communication, increased efficiency, and improved patient satisfaction. Through seamless coordination and interdisciplinary teamwork, nurses and technicians optimize workflow processes, deliver personalized care, and foster a culture of safety and quality within healthcare settings. Key factors contributing to successful nurse-technician collaboration include effective communication, mutual respect, role optimization, and the integration of technology. By nurturing this collaborative partnership, healthcare organizations can enhance patient outcomes, improve clinical practice, and elevate the overall quality of care delivery.